2005
DOI: 10.1037/0022-0663.97.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Number Skills and Knowledge in Children With Specific Language Impairment.

Abstract: The number skills of groups of 7 to 9 year old children with specific language impairment (SLI) attending mainstream or special schools are compared with an age and nonverbal reasoning matched group (AC), and a younger group matched on oral language comprehension. The SLI groups performed below the AC group on every skill. They also showed lower working memory functioning and had received lower levels of instruction.Nonverbal reasoning, working memory functioning, language comprehension, and instruction accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
89
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 71 publications
8
89
2
10
Order By: Relevance
“…for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used Number Skills in Children with SLI 8 to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 96%
See 2 more Smart Citations
“…for a longer period of time than their age-matched peers (Cowan et al, 2005;Donlan et al, 2007;Fazio, 1994Fazio, , 1996Koponen et al, 2006). Nonetheless, the language components which were used Number Skills in Children with SLI 8 to perform these tasks were not clearly identified.…”
Section: Number Skills In Children With Slimentioning
confidence: 96%
“…Children with SLI have a less developed store of arithmetic facts than that of age-matched children (Cowan et al, 2005;Fazio, 1996), a difference which persists during development. For instance, Fazio (1996Fazio ( , 1999 found that children with SLI evaluated at the age of 7 were still less efficient three years later.…”
Section: Number Skills In Children With Slimentioning
confidence: 99%
See 1 more Smart Citation
“…Estas crianças apresentam prejuízo na linguagem oral e inteligência não-verbal dentro ou superior à média (Cowan, Donlan, Newton, & Lloyd, 2005). Apesar das difi culdades apresentadas por essas crianças serem, por defi nição, específi cas na linguagem, o desempenho na matemática também é prejudicado (Donlan, 2007).…”
unclassified
“…Na tarefa de comparação de algarismos multidígitos, o grupo SLI também teve desempenho de acordo com o esperado para sua faixa etária. Cowan et al (2005) investigaram o processamento numérico de crianças SLI entre 7 e 9 anos de idade com o objetivo de investigar as especifi cidades das difi culdades da matemática dessas crianças. As correlações entre os testes de matemática, como contagem e transcodificação, com as tarefas de compreensão oral de linguagem foram maiores que as correlações das tarefas aritméticas com a memória de trabalho (medida por uma tarefa de repetição de pseudopalavras).…”
unclassified